Cryptocurrency – Is It Property?. Issue 2 (26th November 2020) - Low, Gary; Tan, Terence
Abstract : Purpose: To address recent cases and the applicable legal principles relating to cryptocurrency, and to contribute to legal thought in this developing area of law. Design/methodology/approach: This article considers recent cryptocurrency related cases in Singapore, Canada and the United Kingdom, and then considers the implications of the developing law in relation to proper causes of action and issues of practical asset recovery relating to the enforcement of judgments. Findings: The intangible and highly movable nature of cryptocurrency places a premium on decisive asset recovery. The cases also suggest that injunctions remain a useful and effective debt recovery tool, especially when coupled with quick investigative action to trace cryptocurrency payments. However, the law remains unsettled as to the most appropriate cause of action for a claim in cryptocurrency or how a debt in cryptocurrency can be subject to execution. These issues raise the fundamental question of the nature of cryptocurrency, whether it belongs to an existing category of property, or if it is sui generis. Practical implications: Cryptocurrency remains relatively novel and usage is increasing but not widespread. Users of cryptocurrency and lawyers involved in transactions or disputes involving cryptocurrency would benefit from a broader understanding of the legal issues Originality/value: This article provides expert analysis from experienced litigation lawyers familiar with the concepts behind cryptocurrency.